PEDAMPINGAN DAN BIMBINGAN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN ANAK-ANAK DI DESA TELUK ROBAN TAPANULI TENGAH - Suhartono; Sawaluddin Siregar; Zainal Efendi Hasibuan; Gusman Simon (Yayasan Baitul Hikmah al-Zain, 2024)
This service aims to improve the ability to read the Qur'an for children in Teluk Roban Village, Central Tapanuli. The service is approaching the PAR (Participatory Action Research) system method through mentoring and guidance to improve the quality of reading the Qur'an in children in Teluk Roban Village, Sorkam District, Tapanuli Temgah Regency, there needs to be real action in providing various methods to improve children's ability to read the Quran. The conclusion of the dedication to improve the ability of children in Teluk Roban Village in reading the Qur'an shows an improvement. Both in mastering the reading of makhrojul letters and knowing how to read hijaiyah properly and correctly as well as fluency in reading the Qur'an